2021
DOI: 10.3390/ijms22136978
|View full text |Cite
|
Sign up to set email alerts
|

Revising Endosomal Trafficking under Insulin Receptor Activation

Abstract: The endocytosis of ligand-bound receptors and their eventual recycling to the plasma membrane (PM) are processes that have an influence on signalling activity and therefore on many cell functions, including migration and proliferation. Like other tyrosine kinase receptors (TKR), the insulin receptor (INSR) has been shown to be endocytosed by clathrin-dependent and -independent mechanisms. Once at the early endosome (EE), the sorting of the receptor, either to the late endosome (LE) for degradation or back to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…These pathways regulate glucose uptake, lipogenesis, gluconeogenesis, glycogen synthesis, and cellular proliferation 1,2,9 . The active IR is internalized by endocytosis and is either degraded in lysosomes, recycled back to the plasma membrane, or transported into the nucleus where it becomes associated with insulin-responsive genes [10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…These pathways regulate glucose uptake, lipogenesis, gluconeogenesis, glycogen synthesis, and cellular proliferation 1,2,9 . The active IR is internalized by endocytosis and is either degraded in lysosomes, recycled back to the plasma membrane, or transported into the nucleus where it becomes associated with insulin-responsive genes [10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…Regarding AKT activity, it has been recently found that the mTORC1 complex is inactivated in OCRL1 deficient cells ( Madhivanan et al, 2020 ), a defect that triggers a lack of nutrient-sensing ( Wang et al, 2021 ) due to mTORC1 is required for proper insulin signaling ( Saltiel and Kahn, 2001 ). Insulin signaling is also highly dependent on the cell type, something we observed in our experiments, and is associated with insulin receptor trafficking ( Iraburu et al, 2021 ). For instance, the activation of PI3K and pAKT takes place at the plasma membrane as well as in endosomes, with higher activation at the endosome ( Ceresa et al, 1998 ; Iraburu et al, 2021 ), being possible that under LS conditions at least the endosomal signaling, would be affected.…”
Section: Discussionmentioning
confidence: 67%
“…Insulin signaling is also highly dependent on the cell type, something we observed in our experiments, and is associated with insulin receptor trafficking ( Iraburu et al, 2021 ). For instance, the activation of PI3K and pAKT takes place at the plasma membrane as well as in endosomes, with higher activation at the endosome ( Ceresa et al, 1998 ; Iraburu et al, 2021 ), being possible that under LS conditions at least the endosomal signaling, would be affected. Therefore, it is expected that the response to insulin and megalin phosphorylation mediated by GSK3ß are affected in LS cellular models and, in general, cells with decreased function of OCRL1 would be less responsive to insulin.…”
Section: Discussionmentioning
confidence: 67%
“…In the acid late endosome, insulin is dissociated from its receptor and is degraded; the role of IDE in this context is discussed [ 6 ]. Then, the insulin receptor can be recycled back to the plasma membrane [ 94 , 95 ] ( Figure 2 b).…”
Section: Ide and The Insulin/insulin-growth Factor Signaling (Iis) Pa...mentioning
confidence: 99%